2018
DOI: 10.1016/j.jtcvs.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The profound impact of combined severe acidosis and malperfusion on operative mortality in the surgical treatment of type A aortic dissection

Abstract: The combination of severe acidosis (base deficit ≥-10) with abdominal malperfusion was uniformly fatal. Further research is needed to determine whether the identification of extreme risk warrants consideration of alternate treatment options to address the cause of severe acidosis before ascending aortic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 28 publications
(50 reference statements)
1
36
0
Order By: Relevance
“…In our own institutional experience of 282 patients with type A dissection, we found that malperfusion plus a base excess of -10 or worse is rarely survivable, and that malperfusion with a base excess between -5 and -10 is associated with a marked elevation in mortality (Table 1). 2 In fact, in our series, malperfusion and a severe base deficit were worse than receiving cardiopulmonary resuscitation at the time of operation. It appears that base excess has a remarkable predictive ability across patient populations.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…In our own institutional experience of 282 patients with type A dissection, we found that malperfusion plus a base excess of -10 or worse is rarely survivable, and that malperfusion with a base excess between -5 and -10 is associated with a marked elevation in mortality (Table 1). 2 In fact, in our series, malperfusion and a severe base deficit were worse than receiving cardiopulmonary resuscitation at the time of operation. It appears that base excess has a remarkable predictive ability across patient populations.…”
mentioning
confidence: 51%
“…This finding also seems to have surprised the authors themselves, because it contravenes traditional teaching on malperfusion, including our own series, in which mortality was 3-fold higher with malperfusion. 2 Second, and less suprising, is the impressively low rate of subsequent intervention on vessels that were malperfused before type A repair-only 12.5% in this series, and that at 10 years. Third is the overwhelming proportion of patients who were transferred to Stanford from a referring institution for their repair: 93.1%.…”
mentioning
confidence: 70%
“…In these patients, the authors recommended restoration of blood flow to visceral organs via fenestration first, awaiting resolution of the malperfusion syndrome and then performing central aortic repair. Lawton and colleagues [16] studied 282 patients who underwent surgical procedures for acute type A repair and found base deficits greater than -10 as the strongest predictor of mortality. Renal failure was also a strong factor.…”
Section: Commentmentioning
confidence: 99%
“…There are no studies determining the most sensitive marker for preoperative malperfusion. Lactic acid levels above 6 mmol/L [14], as well as base deficit greater than −10 mEq/L [15], have very recently been proposed as cutoff points for an unfavorable outcome, however none of these markers have been analyzed in conjunction with one another, as well as with preoperative pH.…”
Section: Introductionmentioning
confidence: 99%